Penguatan Teologi Aswaja Majelis Taklim Aqaid Khamsin Pekalongan - Muhammad Saifudin Fahmi (UIN K.H. Abdurrahman Wahid Pekalongan, 2018)
This article discusses the effort of Majelis Taklim Aqaid Khamsin (MTAK) Pekalongan in strengthening the theological doctrine Ahlus Sunnah wal Jamaah (Aswaja), especially on the devine attributes. Aswaja's theology has been Indonesian Muslims doctrine for a long time, but later the doctrine has been eroded by the others. It is influenced by the spread of Wahhabist theology by reluctanting to use takwil in understanding the anthropomorphic verses, while the Muktazili’s doctrine tends to upset the Aswaja’s theology. This study uses qualitative methods through interviews and observations. To fortify Aswaja's theology in the community, MTAK provides a provision of understanding to the community in the form of studies around God’s attributes by equipping the congregation with the naqli (tekstual) and aqli (rational) arguments. This study is carried out in the forms: (1) public teaching for all congregations; (2) dialogical guidance; (3) assistance for junior congregations; (4) consolidation of naqli and aqli arguments; and (5) assistance for senior cadres to teach people in various parts of surrounding areas of Pekalongan.